The Quantitative Analysis of bFGF and VEGF by ELISA in Human Meningiomas - Yves Denizot; Rafael De Armas; François Caire; Jean Jacques Moreau; Isabelle Pommepuy; Véronique Truffinet; François Labrousse (Mediators of Inflammation, 2006)
The quantitative analysis of VEGF using ELISA in various subtypes of grade I meningiomas reported higher VEGF contents in meningothelial (2.38±0.62 pg/μg protein, n=7), transitional (1.08±0.21 pg/μg protein, n=13), and microcystic meningiomas (1.98±0.87 pg/μg protein, n=5) as compared with fibrous ones (0.36±0.09 pg/μg protein, n=5). In contrast to VEGF, no difference in the concentrations of bFGF was detected. VEGF levels did not correlate with meningioma grade (1.47±0.23 pg/μg versus 2.29±0.58 pg/μg for 32 and 16 grade I and II, resp), vascularisation (1.53±0.41 pg/μg versus 1.96±0.28 pg/μg for 24 low and 24 high vascularisated tumours, resp), and brain invasion (2.32±0.59 pg/μg versus 1.46±0.27 pg/μg for 7 and 41 patients with and without invasion, resp). The ELISA procedure is, thus, an interesting tool to ensure VEGF and bFGF levels in meningiomas and to test putative correlations with clinical parameters. It is, thus, tempting to speculate that ELISA would also be valuable for the quantitative analysis of other angiogenic growth factors and cytokines in intracranial tumours.